THE MEDIATING ROLE OF ENTREPRENEUR EDUCATION IN THE RELATIONSHIP BETWEEN ENTREPRENEUR CAREER AND ENTREPRENEURIAL SELF-EFFICACY - Khalid, N.; Islam, D.; Lee, H. (Journal of Economic Research & Business Administration, 2019)
The purpose of the study is to examine the role of entrepreneur education in the relationship between entrepreneur career and entrepreneurial self-efficacy. The study serves as substantiation for the previous entrepreneurial career studies and promotes better understanding of factors prompting the antecedents to entrepreneurial behavior. There is a need for more empirical research in this aspect because reviewed literature highlighted a number of problems associated with entrepreneurial education and entrepreneurial career in many nations’ world over and particular the developing countries. The study used survey-based method and SEM-PLS is employed to achieve the research objectives of the study. The data is collected from the manufacturing firms in Pakistan.The empirical evidence on the association between entrepreneurial education, entrepreneurial self-efficacy, and entrepreneurial career with moderating effect of SEN will strengthened previously established models such as the entrepreneurial intention model, which is modification in the theory of planned behavior and entrepreneurial event theory, both of which are linked to the theory of reasoned action. It is assumed that human actions are reasoned, controlled and planned. Thus, action is possible for the consequences of the reflected behavior. The findings are in line with the proposed hypothesized results.The study could offer valuable insights into the stage of entrepreneurial education for a range of stakeholders in Pakistan at particular and the world at large. Perhaps it is among the earliest studies of this kind in Pakistan that examined the effects of entrepreneurial education on students’ attitude toward entrepreneurial career. The outcomes from this study would be of beneficial for variety of interested parties including academicians, policymakers, learning institutions, supervisory bodies and the public in general.